2018
DOI: 10.1039/c8ce01014e
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the effect of mass transfer on the synthesis of silver and gold nanoparticles

Abstract: Silver and gold nanoparticles were prepared using constant reactant concentrations and temperatures, but different process conditions to alter the mass transfer during synthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 57 publications
(64 reference statements)
2
12
0
Order By: Relevance
“…Many studies have tried to demonstrate and simulate the sigmoidal curve for particle formation; the Smoluchowski rate equation 31,32 based on the collision of particles form a statistical perspective, the Kolmogorov-Johnson-Mehl-Avrami expression, 33 for the solid-state phase transformation, the Lifshitz-Slyozov-Wagner model 34 for Ostwald ripening and the relevant diffusion controlled growth model, 16,35 and the Finke-Watzky (F-W) 36 model, for fast autocatalytic surface growth. Since the growth of Cu microparticles has autocatalytic reaction characteristics, the model for the total mass as a function of time in this study is based on the F-W model under the assumption of the pseudo-elementary nucleation and growth steps, and it is expressed as: 37 d½Cu dt…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have tried to demonstrate and simulate the sigmoidal curve for particle formation; the Smoluchowski rate equation 31,32 based on the collision of particles form a statistical perspective, the Kolmogorov-Johnson-Mehl-Avrami expression, 33 for the solid-state phase transformation, the Lifshitz-Slyozov-Wagner model 34 for Ostwald ripening and the relevant diffusion controlled growth model, 16,35 and the Finke-Watzky (F-W) 36 model, for fast autocatalytic surface growth. Since the growth of Cu microparticles has autocatalytic reaction characteristics, the model for the total mass as a function of time in this study is based on the F-W model under the assumption of the pseudo-elementary nucleation and growth steps, and it is expressed as: 37 d½Cu dt…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that the order of reactant addition affects the reaction outcome in the conventional Turkevich synthesis. 15,49 Wuithschick…”
mentioning
confidence: 99%
“…the continued nucleation during particle growth, promotes dispersity in size and shape [46]. To this end, Besenhard et al demonstrated the influence of batch mixing of gold precursor (HAuCl4) and reducing reagent (trisodium citrate) on particle size and dispersity using a fix feed 5:1 ratio (citrate/tetrachloroauric acid) [47]. In contrast to previous reports, smaller nanoparticles with reduced polydispersity were obtained by at-once addition rather than dropwise injection.…”
Section: Figurementioning
confidence: 98%